2021
DOI: 10.1038/s41598-021-92882-w
|View full text |Cite
|
Sign up to set email alerts
|

Examining early structural and functional brain alterations in postpartum depression through multimodal neuroimaging

Abstract: Postpartum depression (PPD) affects approximately 1 in 10 women after childbirth. A thorough understanding of a preexisting vulnerability to PPD will likely aid the early detection and treatment of PPD. Using a within-sample association, the study examined whether the brain’s structural and functional alterations predict the onset of depression. 157 euthymic postpartum women were subjected to a multimodal MRI scan within the first 6 days of childbirth and were followed up for 12 weeks. Based on a clinical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…In contrast to the previous findings, Schnakenberg et al ( 27 ) found no difference between non-depressed and depressed postpartum women regarding rs functional connectivity. The authors controlled the time course of PPD onset to establish the prognostic value of neuroimaging data, since the women had not been depressed at the time of recruitment but might later become depressed at the time of scanning.…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…In contrast to the previous findings, Schnakenberg et al ( 27 ) found no difference between non-depressed and depressed postpartum women regarding rs functional connectivity. The authors controlled the time course of PPD onset to establish the prognostic value of neuroimaging data, since the women had not been depressed at the time of recruitment but might later become depressed at the time of scanning.…”
Section: Resultscontrasting
confidence: 73%
“…In contrast to the studies that found structural correlates of PPD, Schnakenberg et al ( 27 ) failed to detect any difference between depressed and healthy mothers.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Functional neuroimaging (FNI) techniques, such as functional magnetic resonance imaging, electroencephalography, and magnetoencephalography, are powerful tools for studying the human brain and laying methodological foundations for cognitive neuroscience (Li et al, 2019 ). Examining structural and functional changes in the brain through FNI can assist in making accurate clinical diagnoses among individuals experiencing PDD, potentially enhancing treatment approaches for this population and improving prognosis (Schnakenberg et al, 2021 ). However, compared to the relative wealth of data available for major depressive disorders, FNI-based studies focusing on PPD are limited in number and design (Fiorelli et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study examining whether neuronal alterations of PPD in women are detectable right after birth found that despite risk profiles pointing toward developing PPD (and developing PPD 12 weeks postpartum), no structural and functional alterations were found immediately after childbirth in the participants (Schnakenberg et al, 2021). This might suggest that early structural or functional alterations in PPD might be too subtle to be detected with neuroimaging at first but might become more profound in the disease course (Schnakenberg et al, 2021).…”
Section: Neuroanatomymentioning
confidence: 98%